Sociolinguistic Analysis of Taboo Words in Some American Songs (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In every culture, there are many things that are believed to not suitable and appropriate to say on public conversation spoken or written texts. Large number of words are forbidden because they represent the hidden part that should not be tackled publically and give some insights of obscene when they are used in communication. These words are taboo words that is the main concern of this paper that investigates all the major varieties of English taboo words: body movement, death, disease, sex, privacy and discriminatory language. There are some ways to avoid this as using euphemistic and round about ways to deal with such situations.This paper shows the different kinds of taboo words and how these forms can be different through some American songs as well as to show the different functions that taboo words have through using forbidden words in these songs. Through this paper, the findings show that many sociolinguists describe and explain this phenomenon and it is one of universal phenomena that no social group that use language quite at random and using such word are very hard because of their effectiveness emotionally and offensive to other to the public situation.